THE EMERGENCE AND FIRST STAGES OF THE DEVELOPMENT OF COMMON OWNERSHIP - Valentinovich Zarubin, Alexey; Viktorovich Potapenko, Sergey; Eldarovna Adygezalova, Gyulnaz; Yuryevich Kurin, Igor (Revista Inclusiones, 2020)
The study discusses the emergence of relations of common ownership and the first steps of the civil law institution, which originates from the law of Ancient Rome. The connection of communal ownership, joint possession, common ownership, as well as communities based on property (juridical person, partnership and others), and their influence on similar modern institutions is shown. The purpose of the study is to find out how joint possession grew into communal ownership right and then into personal right and common ownership right. What is the role of these processes in the emergence of legal institutions based on the property community? Is there a connection between the modern institute of common ownership and communal ownership right and the Roman institute of common ownership? Are ancient institutions valuable at present?